A lesson to learn from developed countries: The Case of State Branching Deregulation in the US - Guillén, Jorge (Estudios de Economía, 2016)
The era of US state branching deregulation started in 1970 and ended up with theenactment of the Riegle Neal Act of 1994. One of the purposes of the branchingrestriction was to avoid bank concentration. The following paper addressesthe influence of the state deregulation on commercial banks’ efficiency withinthe US. We calculate an indicator of bank efficiency using Data EnvelopmentAnalysis (DEA). The efficiency indicator is used as the primary step to analyzethe effect of state branching law deregulation on bank’s efficiency. The analysisis complemented with a failure prediction model using these DEA scores.